Cultura evangélica e “dominação” do Brasil : música, mídia e gênero no caso do Diante do Trono - Nina Gabriela Moreira Braga Rosas de Castro (2015)
This dissertation aims to further the discussion on the relation of Protestants and secular culture. The subject is the actions of an important actor of the religious realm – the Before the Throne (BT), composed and led by Ana Paula Valadão. The analysis is done by bibliographical research, interviews and participant observation. It is explored the band’s theological emphasis on spiritual warfare/Dominion Theology, their innovations on the music industry and on media, and the gender prescriptions advocated by them. Data on American Protestant context complement the approach. The conclusion is that DT’s initiatives, as well as the success achieved, are due to a subcultural position. Following Christian Smith’s theory, there is a mix of clear differentiation with engagement in the broader society